Apolipoprotein E4 Expression Causes Gain of Toxic Function in Isogenic Human Induced Pluripotent Stem Cell-Derived Endothelial Cells. Issue 9 (September 2019) - Rieker, Claus; Migliavacca, Eugenia; Vaucher, Angélique; Mayer, Fiona C.; Baud, Gilles; Marquis, Julien; Charpagne, Aline; Hegde, Nagabhooshan; Guignard, Laurence; McLachlan, Michael; Pooler, Amy M.
Abstract : Objective: The ApoE (apolipoprotein) allele epsilon 4 is a major genetic risk factor for Alzheimer disease, cardiovascular disorders, and stroke, indicating that it significantly impacts cerebral and vascular systems. However, very little is known about how APOE genotype affects brain endothelial cells, which form a network of tight junctions to regulate communication between the brain and circulating blood factors. Approach and Results: Here, we present a novel model of endothelial dysfunction using isogenic human induced pluripotent stem cell-derived cells harboring different alleles of the APOE gene, specifically ApoE 3/3, 3/4, and 4/4. We show for the first time that ApoE4 expression by endothelial cells is sufficient to cause a toxic gain of cellular dysfunction. Using RNAseq, we found significant effects of ApoE4 on signaling pathways involved in blood coagulation and barrier function. These changes were associated with altered cell function, including increased binding of platelets to ECs with the 3/4 or 4/4 genotype. ApoE4-positive cells exhibited a proinflammatory state and prothrombotic state, evidenced by higher secretion of Aβ (amyloid-β) 40 and 42, increased release of cytokines, and overexpression of the platelet-binding protein VWF (vonWillebrand factor). Immunohistochemistry of human brain Alzheimer disease brains also showed increased VWF expression with the ApoE4/4 genotype. Finally, pharmacological inhibition of inflammation in ECs by celastrol rescued overexpression of VWF in cells expressing ApoE4. Conclusions: These cells provide novel insight into ApoE4-mediated endothelial dysfunction and provide a new platform to test potential therapies for vascular disorders. Abstract : Supplemental Digital Content is available in the text.